Investment decisions are reviewed based on financial literacy and Financial Behavior - Nurrokhmini, Alfiati; Firdaus, Muhamad Yusuf; Kamil, Wisnu Distira (UIN Salatiga, 2023)
The purpose of this study was to determine and measure the influence of financial literacy and financial behavior on investment decisions in students of the Salatiga State Islamic Institute (IAIN Salatiga). The method used in this research is quantitative method, with classical assumption test techniques, multiple linear regression analysis, hypothesis testing, and coefficient of determination with the help of SPSS version 25 software. Data were collected by distributing questionnaires using random sampling techniques distributed to 90 respondents. or student. The results of the study based on t test analysis indicate that financial literacy has no effect on investment decisions. Meanwhile, financial behavior has a positive effect on investment decisions. The results of the study based on the F test analysis showed that financial literacy and financial behavior had a significant and simultaneous effect on investment decision making by students of IAIN Salatiga.